LEARNING MATHEMATICS, DOING MATHEMATICS: A LEARNER CENTERED TEACHING MODEL - Flores, Angel Homero (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2010)
Learning mathematics, Doing Mathematics is a learner-centered teaching proposal under development since 1998 at the Colegio de Ciencias y Humanidades (CCH), a high school system dependant on the National Autonomous University of Mexico. It looks for the creation of a Teaching and Learning Environment (TLE) in which students work and learn collaboratively, with tolerance, respect and responsibility. The main features of this teaching proposal and its theoretical and philosophical foundations are presented.